Eupatorium and Weedicides - Rai, S. N. (Indian Forester, 1976)
Eupatorium odoralum has become a very obnoxius weed in the Western Ghat region of the country, particularly in parts of Karnataka and Kerala States. It has been colonising not only the open patches amidst forest stands, but also grassy blanks and barran areas at lower elevations. Its impact on natural regeneration, success of artificial regeneration and productivity of commercial crops is of considerable magnitude. Chemicals control of the weed has proved uneconomic and therefore, manual removal with good cover crop remain the only alternative.